THU0504 ROTATOR CUFF CALCIFICATION AND SHOULDER PAIN: A CLINICAL AND ECHOGRAPHIC STUDY OF 465 PATIENTS. (June 2019) - Luisa, Orlik; So, Alexander; Alain, Farron; Zufferey, Pascal
Abstract : Background: Shoulder pain is a common cause for medical consultation and is commonly linked to lesions of the rotator cuff. Rotator cuff calcification (due to BCP crystal deposition) is also a common finding and can give rise to chronic pain as well as acute inflammatory episodes Objectives: The goal of the study was to compare the clinical and the echographic characteristics of patients with BCP calcification in the rotator cuff and shoulder pain to those with no signs of calcification Methods: A retrospective case-control study of 465 patients whose primary complaint was shoulder pain presenting between 1997 and 2011 and seen by one rheumatologist. 125 patients who had rotator cuff calcification (RCC) were identified and constituted the study group. We compared the patients with RCC with 125 patients without calcification who were randomly extracted from the same registry which constituted the control group. All had detailed demographic and clinical documentation as well as a precise description of the echographic findings. Subgroups were defined according to the type and the duration of symptoms (Hyperacute painful shoulder, subacute inflammatory symptoms and chronic mechanical pain). Short-term response (up to 6 weeks) to treatment was also analyzed for the two first subgroups Results: 25% of the patients consulting for shoulder pain had evidence of RCC as demonstrated by ultrasound. Hyperacute and subacute inflammatory symptoms were not linked to calcification (Hyperacute: 16 pts with 13pts without (p value : ns), subacute: 32 pts in both groups). The mean age (54 years) and female predominance (60%) were also similar in patients with or without calcification. However, patients with hyperacute painful shoulder with RCC were younger (mean years: 49 against 58 years; p: 0.007). None were <35 or > 60 years old and 75% of them were females. In 60% of cases of hyperacute painful shoulder linked to calcification, the acute flare was the first shoulder complaint compared to <30% in the overall sample (p: <0.0001). More than a 1/3 of the patients with RCC (35% in chronic and 43% in acute symptom groups) had no other echographic lesion compared to < 5% of patients without RCC. Calcifications were rarely associated with partial or total rotator cuff rupture (<10% against 25% without, p: 0.007). Steroid infiltrations were mostly performed with rapid short-term response in the acute and subacute groups linked to calcification: 15/16, 24/34 against 4/13 p:0.001, 10/34 p:0.001 without calcification. Surgery was necessary in 7/101 pts with chronic symptoms without calcification against only 1/95 when calcifications were present (p:0.03). Conclusion: Clinical and demographic data cannot clearly predict the presence of RCC in patients presenting with shoulder pain. However, acutely symptomatic RCC is found preferentially in middle aged women, often with no degenerative or traumatic echographic lesions. Steroid infiltration appears to be the treatment of choice when acute inflammatory symptoms linked to RCC are present Disclosure of Interests: Orlik Luisa: None declared, Alexander So Consultant for: SOBI, Grunenthal, Speakers bureau: Grunenthal, Farron Alain : None declared, Pascal Zufferey: None declared